Internal jugular vein catheterization: A comparison between ultrasound guided technique with landmark guided technique - Singh, Shashi Ram; Yadav, Rajesh; Keyal, Niraj Kumar; Pathak, Vipul Vivek (Med Phoenix, 2022)
Introduction: Central venous cannulation is frequently performedprocedures to gain access to the central vein. With increased use ofultrasonography to guide cannulation, the success rate has improved andit has decreased the time required for cannulation and complications. Theaim of the study was to compare ultrasound guided technique (USG) andlandmark technique (LMG) in Internal jugular vein.Materials and Methods: This study was conducted in National MedicalCollege and Teaching Hospital, Birgunj from July 2019 to July 2020. Ethicalclearance (NMC/420/075/076) was obtained from institutional reviewcommittee of NMC Birgunj. Total of 60 patients were randomly allocatedinto two groups; ultrasound group (USG) landmark group (LMG) underwentlandmark guided catheterization. Access time, number of attempts forsuccessful cannulation and incidence of various complications werecompared between groups. Data analysis was done with Statistical Packagefor Social Science version 22.Result: The study was conducted on 60 patients, divided randomly intotwo groups with 30 patients in each group. The mean age for LMG was48.57±16.08 years and for USG was 50.03±13.36 years. Out of 60 patients,61.7% were male and 38.3% were female. The mean of neck dimensionfor LMG and USG was 35.95±6.327 and 35.67±6.194 cm respectively. Themean distance under LMG and USG was 19.07±1.780 and 18.33±2.368cm respectively. The mean access time taken for LMG and USG was403.10±98.111 and 217.57±75.408 seconds respectively (p